Black Emotions Matter: Understanding the Impact of Racial Oppression on Black Youth’s Emotional Development: Dismantling Systems of Racism and Oppression During Adolescence - Lozada, Fantasy T.; Riley, Tennisha N.; Catherine, Evandra; Brown, Deon W. (Journal of research on adolescence, 2022)
Black US Americans’ emotions are subject to stereotypes about the anger and aggression of Black people. These stereotypes are readily applied to Black adolescents’ emotions. The purpose of this conceptual paper is to operationalize racial oppression in the emotional lives of Black adolescents through an application of García Coll et al.'s (1996) ecological model for minority youth development. We specify emotionally inhibitive features of Black adolescents’ schools, the adaptive culture of Black Americans in the United States that responds to emotional inhibition, Black families’ emotion socialization processes, and Black adolescents’ emotional flexibility behaviors. Throughout, we integrate findings from research on Black adolescents’ emotional adjustment with research on cultural values, emotion and racial socialization, school‐based racial experiences, and theory on emotion and cultural navigation.